A new dimension in patent foramen ovale size estimation. Issue 7 (7th July 2020) - Demulier, Laurent; Paelinck, Bernard Pierre; Coomans, Ilse; Hemelsoet, Dimitri; De Backer, Julie; Campens, Laurence; De Wolf, Daniel
Abstract: Background: Detailed multidimensional assessment of patent foramen ovale (PFO) size with transesophageal echocardiography (TOE) may help to determine PFO pathogenicity in cryptogenic stroke patients. We explored the potential additive value of Live xPlane and three‐dimensional (3D) TOE anatomical PFO sizing techniques. Methods: Imaging data of 45 patients who underwent a 3D TOE‐assisted percutaneous PFO closure were studied. The two‐dimensional (2D) PFO separation distance and right‐to‐left (RL) contrast shunt magnitude were assessed on preprocedural TOE recordings. Peri‐procedural measurements of the triangular anatomical PFO opening (base, height, and area) were performed after positioning of a stiff guidewire (SW) through the PFO, using Live xPlane imaging and 3D Zoom mode. Results: The PFO SW base appeared on average 5 times larger than the preprocedural 2D PFO separation (median difference [IQR] = 13[5] mm; P < .001). For a same PFO separation, the width of the PFO base may vary significantly. The PFO SW base was significantly larger in patients with a large versus a small‐to‐moderate PFO RL contrast shunt (18 vs 15 mm; P = .007) and in those with a spontaneous versus a provoked shunt (18 vs 14 mm; P = .003). Conclusion: Live xPlane and 3D Zoom TOE allow peri‐procedural measurement of the largest dimension of a PFO, which is the PFO base. Patients with a large or spontaneous RL contrast shunt appear to have a larger PFO base. The anatomical PFO base dimension may be taken into account for optimization of device and patient selection strategies.